The Philosophy of Naming Universities Based on Indonesian Figures and its Relevance to Impactful Campus Development - Santoso, Heri; Kuswanjono, Arqom; Ainia, Dela Khoirul; Putri, Kusuma (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2026)
This article examines the philosophical meaning of naming universities in Indonesia based on figures from the archipelago and its relevance to the development of the concept of impactful campuses. This study departs from the assumption that the name of a university is not merely an administrative identity, but a living symbol that embodies values, ethics, and educational ideals. This research uses a philosophical approach with descriptive-interpretative methods to interpret the values embodied in Nusantara figures such as Mahapatih Gadjah Mada, Prabu Airlangga, Prabu Udayana, Sultan Hasanuddin, Pangeran Diponegoro, and Kapitan Pattimura. The results of the study show that naming universities after Nusantara figures carries a philosophical meaning from the ethical perspective, such as the values of spirituality, independence, nationalism, dedication, unity, prosperity, harmony, determination, sovereignty, moral courage, solidarity, and people’s leadership. These values have substantive relevance for the development of impactful campuses, as they provide a normative framework for internalizing values in fostering the application of the three pillars of higher education, academic culture, and university governance. This article affirms that an impactful campus is not solely determined by policy achievements or performance indicators, but rather by the character building of the academic community established in the values of nationalism, social responsibility, and intellectual sovereignty.